A Hyperdynamic Arteriovenous Fistula Aneurysm After Long Time Renal Transplantation. (February 2023) - Klüsch, Victoria; Aper, Thomas; Sonnenschein, Kristina; Becker, Lena Sophie; Umminger, Julia; Haverich, Axel; Rustum, Saad
We report a case of a 53-year old male with a giant aneurysm of an arteriovenous fistula (AVF) in the left arm, which was created several years ago due to renal failure secondary to Alport's syndrome. The AVF had not been used for over 38 years after successful renal transplantation at the age of 15. In the following, the patient underwent a regular follow-up with regularly visits by physicians and/or a nephrologist. A growth of the unused AVF over time was noticed, but surgical resection was not performed or recommended. Finally, the patient presented in our clinic with a severe hyperdynamic AVF aneurysm, so that we decided to treat the aneurysmal AVF surgically including exclusion the arteriovenous anastomose and reconstruction of the left arm vessels. Conclusion: Closure of arteriovenous fistula should be considered in patients who underwent successful renal transplantation to avoid potential complications that may result from the presence of unused fistula especially, in patients who are predisposed to aneurysm formation in the future.